The Evolution of Green Bonds and Sustainable Finance in Public Sector Budgeting and Development Projects - Celestin, Mbonigaba; Mishra, Dr Anjay Kumar (Journal of Advanced Research in Humanities and Social Sciences; Vol 12 No 1 (2025): Journal of Advanced Research in Humanities and Social Sciences, 2025)
Purpose: This paper investigates the evolution of green bonds and sustainable financing within public sector budgeting and development initiatives from 2020 to 2024. The study aims to examine key developments in green bond issuance, assess their impact on sustainable finance, and identify barriers to their integration into public sector budgeting. Methodology: A mixed-methods approach was employed, combining document analysis, empirical reviews, and statistical modeling. Regression analysis was utilized to explore the relationship between green bond investments and financial returns, while chi-square and paired t-tests were used to assess geographical disparities in green bond adoption and the influence of government incentives on investment growth. Findings: Regression analysis revealed a strong positive correlation (R² = 0.87) between green bond investments and financial returns, with ROI increasing from 3.5% in 2020 to 5.8% in 2024.A chi-square test identified significant regional disparities, with Europe and Asia-Pacific leading in adoption, while Africa lagged due to weaker regulatory frameworks. A paired t-test indicated that government incentives significantly boosted green bond investments, leading to a 30-50% increase in funding for sustainable projects. Conclusions: Green bonds have proven to be an effective financial tool for achieving sustainability goals. However, their success requires coordinated policies, enhanced transparency, and stronger financial incentives. The study recommends improving regulatory frameworks and leveraging technology for more accurate impact assessment to enhance the effectiveness of green bonds in public finance.